Charles Dicken : Oliver Twist - Dickens, Charles, 1812-1870.; BBC Worldwide (Burbank, CA : Warner Home Video, 2009)
After escaping from the dreary workhouse where he has spent his childhood, Oliver runs away to London, only to fall in with Artful Dodger, Fagin, and their gang of young thieves. It is only with the revelation of Oliver's true identity that his troubles finally end.
Based on the novel by Charles Dickens.
Eric Porter, Michael Attwell, Scott Funnell, David Garlick, Amanda Harris, Godfrey james, Frank Middlemas and Ben Rodska.
113458
Keywords: Dickens, Charles, -- 1812-1870 -- Film and video adaptations; 1800-1899; London (England) -- Social life and customs -- 19th century; Film adaptations